Et grundtvigiansk fakultet - Elstad, Hallgeir (Dansk Teologisk Tidsskrift, 2011)
The aim of this article is to shed light on the founding phase of the history of The Faculty of Theology in Christiania (Oslo). Together with the University of Oslo the Faculty celebrates its 200 years anniversary in 2011. The University was the first cultural institution in Norway and played a decisive role in the nation building. The history of the Faculty of Theology is tightly interwoven with that of the University. The initial phase of the Faculty’s history may be characterized ‘Grundtvigian’. Despite of the break with Denmark in 1814, the Danish cultural influences were still strong.